Impact of amylose content on starch physicochemical properties in transgenic sweet potato. (20th May 2015) - Zhou, Wenzhi; Yang, Jun; Hong, Yan; Liu, Guiling; Zheng, Jianli; Gu, Zhengbiao; Zhang, Peng
Highlights: Impact of amylose content on starch physicochemical properties was studied. Waxy and high-amylose starches had different chain length distribution from the normal starch. The transition from the type-A crystal form of low-amylose starches to the type-B crystal form of high-amylose staches was revealed. High amylose increased the shear stress resistance of starch gel after gelatinization. Novel starches for various applications were developed in sweet potato. Abstract: The intrinsic relationship between amylose content and starch physicochemical properties was studied using six representative starch samples (amylose content 0–65%) produced from transgenic sweet potato (cultivar Xushu22). The transgenic lines (waxy and high-amylose) and wild-type (WT) sweet potatoes were analyzed for amylose content, particle size and chain length distribution, X-ray diffraction analysis, thermal characteristics, pasting and rheological property. Compared to the WT starch, the waxy and high-amylose starches showed larger average granule sizes and had fewer short chains and more medium and long chains. X-ray diffractogram analysis revealed that high-amylose starches show a type-B crystal form with a markedly decreased degree of crystallinity in contrast to the type-A crystal form of the WT and waxy starches. In the high-amylose sweet potato starches, the rise of setback value and the reduction of breakdown value led to the high shear resistance as indicated by the higher G ′, G ″, and tan  δ from the oscillation test. Δ H was not found to be decreased with the reduction of crystallinity. The shear stress resistance of starch gel after gelatinization was also enhanced as amylose content increased. Principal component analysis also confirmed that the amylose content greatly influenced the starch structure and properties, e.g., storage modulus, setback value, and average chain length. Thus, our study not only shed light on how amylose content affects starch properties but also identified novel starches that are available for various applications.